Mathematical modelling on servo-valve line hydraulic system - Haidar Bin Junidi (Nanyang Technological University, 2024)
The design and optimization of hydraulic systems in marine and industrial applications are critical for enhancing operational efficiency and ensuring mechanical stability. This study explores the impact of parametric variations on the output characteristics of hydraulic systems, with a focus on pipeline parameters such as length and diameter and effects of an accumulator. Utilizing a mathematical model of an electro-hydraulic servo system, detailed analysis was conducted a to investigate the system's dynamic response to parametric changes.